2018
DOI: 10.4314/bajopas.v10i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of respiratory syncytial virus infection in children (0-5 years) attending institute of child health Banzazzau Zaria Kaduna State

Abstract: Serological survey was carried out among children attending Institute of Child Health (ICH) Banzazzau Zaria Kaduna, State, to determine the prevalence of Respiratory Syncytial Virus IgM antibodies. Ninety-one blood samples of children aged 0 clinic of Ahmadu Bello University Teaching Hospital Zaria (ICH Banzazzau). Respiratory s virus IgM antibody level was measured using commercial ELISA kit obtained from DIAGNOSTIC AUTOMATION, INC. Of the ninety seropositive for Respiratory Syncytial Virus. There was male pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
5
3
0
Order By: Relevance
“…The statistical association between RSV IgM and gender, age, or any of the symptoms considered was not significant ( p > 0.05). Similar reports by previous researchers had shown that gender was not significantly associated with susceptibility to HRSV infection 30,31 . Also similar to this study, no statistical association between age, respiratory infection symptoms, and RSV infection was reported by Sulaiman et al 31 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The statistical association between RSV IgM and gender, age, or any of the symptoms considered was not significant ( p > 0.05). Similar reports by previous researchers had shown that gender was not significantly associated with susceptibility to HRSV infection 30,31 . Also similar to this study, no statistical association between age, respiratory infection symptoms, and RSV infection was reported by Sulaiman et al 31 …”
Section: Discussionsupporting
confidence: 90%
“…A low seroprevalence was recorded for RSV IgM with 15/200 (7.5%) among the studied children. In contrast, a similar study reported a higher seroprevalence of RSV IgM (47.3%) among children in Zaria, Nigeria 31 . The statistical association between RSV IgM and gender, age, or any of the symptoms considered was not significant ( p > 0.05).…”
Section: Discussionmentioning
confidence: 65%
“…This is in tandem with studies from Nigeria and other part of the world where fever and cough were reported as the commonest symptoms seen in ALRTIs caused by RSV [22]. In Ibadan, fever was seen in 78% while cough was seen in 82% of ALRTIS caused by RSV [20]. Similarly, a study conducted in Zaria found that fever and cough were seen in 82% and 79% of children with RSV infection respectively [25].…”
Section: Discussionsupporting
confidence: 76%
“…This prevalence obtained is close to 23.5% reported in a sero-epidemiological study of respiratory syncytial virus among children in Ibadan, South West, Nigeria [19]. However, this finding is lower than 34.6% reported in another study in Ibadan among children attending secondary health facility for ALRTIs [20]. In Abeokuta a prevalence of 5.4% was reported among children under the age of five years attending paediatric outpatient for ALRTI [21].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation